Complementary feeding practices among mothers of children aged six months to two years admitted in a tertiary care hospital - G. N., Madhu; S., Harish (International Journal of Contemporary Pediatrics, 2017)
Background: Optimal infant and young child feeding (IYCF) is an evidence-based measure for improving child nutrition and child survival. After 6 months of exclusive breast feeding, introduction of appropriate complementary feeds is essential. To ensure desirable growth and development of children, complementary feeding should be timely, culturally acceptable, nutritionally adequate, safe and responsive. Objective of this study was to assess the complementary feeding practices among the mothers of children between 6 months and 1 year of age with respect to the time of introduction, quantity and quality. Methods: This is a hospital based cross sectional survey among the mothers of children aged 6 months to 2 years admitted in pediatric wards at KIMS Bangalore during a study period of 6 months. A predesigned questionnaire was used for the collection of data. Details including socio demographic profile of the family and feeding practices of the infant were collected in detail. Results: Out of the 200 participants, 59% were males. 74.5% of the respondent mothers were housewives. Complementary feeds were started at appropriate time in 64.5% of the cases. The feeds were adequate in amount and frequency in 34.5% of the children. Bottle feeding was noted in 33.5% of the cases. Conclusions: Apart from the timely introduction of complementary feeds to infants, emphasis also should be given to the adequacy and quality of the feeds with respect to nutrients. Health professionals should focus on counseling the mothers on appropriate complementary feeding during antenatal, delivery, postnatal, and immunization services.